A Simple Method of Preparation of High Silica Zeolite Y and Its Performance in the Catalytic Cracking of Cumene - Zhanjun Liu; Chenxi Shi; Dan Wu; Shixuan He; Bo Ren (Journal of Nanotechnology)
A series of high silicon zeolites Y were prepared through direct synthetic method by using silica sol as the silicon source and sodium aluminate as the aluminum source. The effects of alkalinity and crystallization time of the process of synthesis were investigated. To separately reveal the crystalline structure, element content, morphology, and surface areas, the as-synthesized zeolite Y was characterized by powder X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscopy (SEM), and N2 adsorption-desorption isotherms (BET). The results show the as-synthesized zeolite Y with high relative crystallization and uniform morphology; the SiO2/Al2O3 ratio was about 4.54~6.46. For an application, the zeolite cracking activity was studied with cumene as the probe molecules.